Utilization of Whey as a Cooking Syrup Medium in the Preparation of Chhana Based Sweet - ’Rasogolla’ - Acharya, Pushpa P; Kanth, Sandeep K. (Tribhuvan University Journal, 2010)
Rasogolla was prepared in laboratory by using standardized pasteurised milk produced from Biratnagar Milk Supply Scheme (BMSS), Dairy Development Corporation (DDC), Biratnagar. It was analyzed for sensory, chemical, biochemical and microbiological attributes. Key words: Chemical and microbiological analysis; dairy milk; Sensory parameters; Storage of rasagolla; Whey utilization Tribhuvan University Journal Vol. XXV, No. 1, 2005 Page:149-158 Uploaded date: 26, September, 2010